2013
DOI: 10.1007/s00775-013-1059-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of divalent transition metal ion paraCEST MRI contrast agents

Abstract: Transition metal ion-based paraCEST agents (TM-CEST) are a promising new class of compounds for MRI contrast. Members in this class of compounds include paramagnetic complexes of FeII, CoII and NiII. The development of the coordination chemistry for these paraCEST agents is presented with an emphasis on the choice of azamacrocycle backbone and pendent groups with the goals of controlling oxidation state, spin state and stability of the complexes. CEST spectra and images are compared for different macrocyclic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(127 citation statements)
references
References 90 publications
(188 reference statements)
4
122
1
Order By: Relevance
“…Most of these paraCEST agents incorporate lanthanide ions that are potentially toxic, limiting intravenous administration to concentrations below their CEST detection limit within in vivo tissues . Some paraCEST agents incorporate nontoxic metals, but their oxidation state for CEST MRI are relatively unstable, which may compromise their practical utility . Yet many of the 42 paraCEST agents that have been reported have shown good utility for molecular imaging studies of small animal models …”
Section: Exogenous Cest Agentsmentioning
confidence: 99%
“…Most of these paraCEST agents incorporate lanthanide ions that are potentially toxic, limiting intravenous administration to concentrations below their CEST detection limit within in vivo tissues . Some paraCEST agents incorporate nontoxic metals, but their oxidation state for CEST MRI are relatively unstable, which may compromise their practical utility . Yet many of the 42 paraCEST agents that have been reported have shown good utility for molecular imaging studies of small animal models …”
Section: Exogenous Cest Agentsmentioning
confidence: 99%
“…48,49 Our previous work has shown that Fe(II), Co(II) and Ni(II) complexes produce highly shifted and often relatively narrow proton resonances to give complexes that function as paraCEST agents. 26,5052 For these transition metal ions, contact (through-bond) contributions to the hyperfine shifts are expected to be substantial. 53 Thus hyperfine shifts can be quite large even for paramagnetic metal ions such as Co(II) and Fe(II) that have relatively small magnetic moments in comparison to lanthanides that demonstrate highly shifted proton resonances such as Dy(III) and Tm(III).…”
Section: Introductionmentioning
confidence: 99%
“…5760 For example, as reported by our group, all of the Fe(II) and Co(II) complexes of TACN and CYCLEN appended with amide groups give broad proton resonances due to their structural fluxionality. 52 In contrast, heterocyclic pendents attached to a TACN framework generally give more rigid Fe(II) and Co(II) complexes. 26,50,51 Additionally, while CYCLEN-based Ln(III) complexes often produce several structural isomers detectable on the 1 H NMR time-scale, 57,59 it is preferable to prepare new complexes that exist in a single diastereomeric form in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…28 In contrast, the rate constants for exchange of NH protons of amide pendents are low, ranging from 300 to 800 s −1 at neutral pH. 20 ParaCEST agents with amide pendents generally undergo base-catalyzed proton exchange with CEST peak intensity and corresponding exchange rate constants increasing with pH.…”
Section: Discussionmentioning
confidence: 99%
“…1920 In particular, CEST MRI is of special interest due to the intrinsic responsiveness of the exchangeable protons of the contrast agent to the environment. 21 These exchangeable protons are key to producing contrast through decreasing the water proton resonance intensity.…”
Section: Introductionmentioning
confidence: 99%